Acceptance Of Mochi With Substitution Of Beet Flour Substitution - Athira Demitri; Icha Azzah Nabillah; Tuty Hertati Purba; Eka Nenni Jairani; Lutfi Henderlan Harahap (Lembaga Pengembangan Kinerja Dosen, 2024)
Mochiis a typical Japanese food which is quite famous in Indonesia for its chewy texture and semi-wet nature. Mochi comes from the Japanese word for muaci. Objective: To determine the physical and chemical characteristics (color, aroma, taste, texture, water content, ash content, fat, folic acid, potassium) of mochi with the substitution of beetroot flour. Method: This type of research is an experimental study with a Completely Randomized Design (CRD), with 4 treatments and 2 repetitions, resulting in 8 experimental units in making mochi with beet flour substitution. The research was carried out in September 2023 at the Helvetia Health Institute, then chemical tests were carried out at the Bioprocess Engineering Laboratory of the Medan Industrial Chemical Technology Polytechnic. In this research, there are hedonic and hedonic quality then proximate tests. Data analysis used Anova and continued with the Duncan test. Results: The hedonic test shows that the F1 formula is the best formula with an average hedonic test value of 3.80 in the like category, while the hedonic quality test shows that the F1 formula is the best formula with an average hedonic quality test value of 3.72 in the purple, aroma category. typical beet flour, sweet taste and chewy texture. The nutritional content of mochi is 20.72% water content, 3.42% ash content, 8.36% fat, 0.186 mg/gr folic acid, and 8.753 mg/gr potassium. Conclusion: The most preferred mochi based on hedonic tests and hedonic quality is the F1 formulation which can be used as an additional food for teenagers and pregnant women because it contains folic acid (0.186 mg/gr).